2019
DOI: 10.1002/bjs.11118
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gut hormones, glycaemic response and symptoms after oesophagectomy

Abstract: Background: Oesophagectomy is associated with reduced appetite, weight loss and postprandial hypoglycaemia, the pathophysiological basis of which remains largely unexplored. This study aimed to investigate changes in enteroendocrine function after oesophagectomy.Methods: In this prospective study, 12 consecutive patients undergoing oesophagectomy were studied before and 10 days, 6, 12 and 52 weeks after surgery. Serial plasma total fasting ghrelin, and glucagon-like peptide 1 (GLP-1), insulin and glucose relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…Prevalence estimates range widely due to differing diagnostic criteria used, though the occurrence of severe hypoglycemia among postbariatric patients may be as high as 29% to 39% of patients undergoing Roux-en-Y gastric bypass (RYGB) and 10% to 23% of those undergoing vertical sleeve gastrectomy ( 9-12 ). Similar clinical presentations have been described following gastrectomy ( 13 ), esophagectomy ( 14 ), and Nissen fundoplication ( 15 ). Patients present at least 6 months postoperatively with frequent postprandial episodes of hypoglycemia accompanied by neuroglycopenic signs and symptoms, including altered mental status, visual changes, motor incoordination, loss of consciousness, and seizures, putting patients at risk for injury or death from falls, motor vehicle accidents, or prolonged hypoglycemia, and rendering many unable to drive, work, live alone, or care for dependents.…”
supporting
confidence: 57%
“…Prevalence estimates range widely due to differing diagnostic criteria used, though the occurrence of severe hypoglycemia among postbariatric patients may be as high as 29% to 39% of patients undergoing Roux-en-Y gastric bypass (RYGB) and 10% to 23% of those undergoing vertical sleeve gastrectomy ( 9-12 ). Similar clinical presentations have been described following gastrectomy ( 13 ), esophagectomy ( 14 ), and Nissen fundoplication ( 15 ). Patients present at least 6 months postoperatively with frequent postprandial episodes of hypoglycemia accompanied by neuroglycopenic signs and symptoms, including altered mental status, visual changes, motor incoordination, loss of consciousness, and seizures, putting patients at risk for injury or death from falls, motor vehicle accidents, or prolonged hypoglycemia, and rendering many unable to drive, work, live alone, or care for dependents.…”
supporting
confidence: 57%
“…Prior longitudinal work in an esophagectomy cohort has shown that the exaggerated enteroendocrine response corresponds with important appetitive symptoms, such as early satiety, and correlates with Sigstad score (11). In this study, treatment with Octreotide LAR was associated with a 30% relative reduction in Sigstad score, reflective of acute post-prandial symptom burden.…”
Section: Discussionmentioning
confidence: 51%
“…This limits the ability to appropriately target treatment to patients who are most likely to derive benefit. Recent developments in our understanding of how alterations in gut-brain axis signaling may be implicated in the pathophysiology of post-esophagectomy symptomatology and malnutrition (11), should enable a more systematic approach to therapeutic interventions. Moreover, while studies at least suggest a compelling rationale for long-term nutritional benefit with the use of Octreotide LAR, through mitigation of the exaggerated post-operative gut hormone response, this remains to be proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-operative plasma ghrelin was lower than the pre-operative concentrations in esophageal cancer patients, which slightly recovered in 6–24 months. There was no relationship between circulating ghrelin and clinicopathologic features of tumor (45, 108).…”
Section: Oesophageal Cancermentioning
confidence: 91%